Business models classification in Industry 4.0 - Niemczyk, Jerzy; Trzaska, Rafał (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The purpose of the research, the results of which are presented here, was to check, based on the analysis of the literature in the field of management science, proposals to identify the types of business models appropriate for solutions forced by technological, technical, economic and social changes related to the industrial revolution commonly referred to as 4.0. It should be added that the adopted analytical perspective is the perspective from the point of view of an enterprise implementing solutions 4.0 or arising entirely in the conditions of a new economy.The chapter has three basic parts. The first part contains the proposal adopted by the authors, based on a review of current literature, to include Industry 4.0 in economic and management perspectives. The second part contains the proposal for the definition of the business model adopted in the chapter, which in the authors’ opinion is appropriate for the changes generated by Industry 4.0. The third part is the results of the review of the results of research present in the literature on the types or business models corresponding to changes 4.0.The considerations contained in the chapter revolve around a research problem boiling down to seeking the answer to the question whether Industry 4.0 generates completely new types of business models, or is it just adapting existing business models to new conditions?